2021
DOI: 10.1029/2021je006895
|View full text |Cite
|
Sign up to set email alerts
|

Early Habitability and Crustal Decarbonation of a Stagnant‐Lid Venus

Abstract: The evolution of Venus is still in many ways a mystery. Despite its similarity to Earth in terms of size and bulk composition (e.g., Lécuyer et al., 2000), the atmospheric 2 CO E mass of Venus is larger by more than five orders of magnitude (Donahue & Pollack, 1983). Whether Venus' atmosphere was 2 CO E -rich early in its evolution, or whether, and how, it diverged from Earth's atmosphere later in its evolution is a matter of debate (e.g.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 93 publications
0
22
0
Order By: Relevance
“…Modelling results from a coupled interior-atmosphere model of a stagnant lid Venus assuming different planetary albedos, after the solidification of the magma ocean (Höning et al 2021). The model assumes an initially thin atmosphere containing only the present-day N 2 inventory.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling results from a coupled interior-atmosphere model of a stagnant lid Venus assuming different planetary albedos, after the solidification of the magma ocean (Höning et al 2021). The model assumes an initially thin atmosphere containing only the present-day N 2 inventory.…”
Section: Figmentioning
confidence: 99%
“…3-D general circulation models by Way and Del Genio (2020) indicate that cloud feedbacks of a slowly rotating early Venus would result in a planetary albedo between 0.5 and 0.6, sufficiently high to potentially allow for liquid surface water on early Venus. Coupled atmosphere-interior models that include silicate weathering, carbonate burial and metamorphic decarbonation (Höning et al 2021) indicate that for planetary albedos in this range an early stagnant lid Venus could have been habitable for up to 1 Gyr, followed by evaporation of water and dramatic rise of atmospheric CO 2 (Fig. 9).…”
Section: Figmentioning
confidence: 99%
“…This is an important point, since Gaillard & Scaillet (2014) showed that volcanic degassing chemistry is dependent upon atmospheric pressure. In addition, the role of land and seafloor weathering and their ability to remove CO 2 from the atmosphere is an important consideration for whether the planet is in a modern Earth-like plate tectonic mode with land and seafloor weathering (e.g., Walker et al 1981;Berner & Caldeira 1997;Krissansen-Totton et al 2018;Graham & Pierrehumbert 2020) or even a stagnant lid (e.g., Foley & Smye 2018;Höning et al 2021). These works demonstrate that the exact conditions for producing a runaway greenhouse will require sophisticated climate modeling that is outside the scope of the present work.…”
Section: Lip Simultaneity In the Context Of A Superimposed Climatic S...mentioning
confidence: 99%
“…If liquid water was present at the surface of Venus in its past then the planet’s slow rotation rate would have enabled a stabilising cloud-climate feedback mechanism to be established 17 , maintaining habitable surface conditions despite the increasing Solar luminosity over time. This phase of habitability could have lasted for up to ~900 Myrs if Venus has always been in a stagnant lid tectonic regime 18 , or if early Venus had Earth-like plate tectonics then this habitable period could have lasted for up to 4 Gyrs, until runaway greenhouse was instigated by voluminous magmatism 17 . In contrast, other modelling has suggested that, due to its proximity to the Sun, Venus could never have cooled sufficiently for liquid water to condense at the surface following its magma ocean phase, and thus a stabilising cloud feedback could never have been established 19 .…”
Section: Introductionmentioning
confidence: 99%